A Study to Assess the Prevalence and Risk Factors of Labor-Onset Hypertension among Women in Intranatal Period Admitted in Selected Hospital, Assam - Ampi Tage; Monika Nongmeikapam (Indian Journal of Community Medicine)
Background: Labor-on-set hypertension itself is a very new study, and it is an intriguing subject for researchers to understand its impact and outcome during labor. To assess the prevalence and risk factors of labor-onset hypertension among women in the intranatal period and also to find the association between prevalence and risk factors with the demographic variables. Materials and Methods: The research design adopted in this study is a descriptive cross-sectional design. Data were collected using a non-probability convenience sampling technique. Results: The study revealed that the prevalence of labor-onset hypertension among 219 women in the intranatal period was 67 (30.6%) who had stage II hypertension and 12 (5.5%) who had risk factors for labor-onset hypertension. The demographic variables occupation and dietary habits had shown a statistically significant association with the prevalence of labor-onset hypertension. The demographic variable age had shown a statistically significant association with risk factors for labor-onset hypertension. Conclusion: This study concluded that most of the women in the intranatal period were recorded with stage II hypertension and the presence of risk factors among women in the intranatal period. There was also a significant association between the prevalence and risk factors of labor-onset hypertension and demographic variables.